2017
DOI: 10.1146/annurev-linguistics-011516-034226
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Pathways Between Socioeconomic Status and Language Development

Abstract: Children from low-income backgrounds consistently perform below their more advantaged peers on standardized measures of language ability, setting long-term trajectories that translate into gaps in academic achievement. Our primary goals in this review are to describe how and why this is so, in order to focus attention on ways to enrich early language experiences across socioeconomic strata. We first review the literature on the relation between socioeconomic status (SES) and language ability across domains in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
169
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(213 citation statements)
references
References 148 publications
11
169
2
8
Order By: Relevance
“…These studies revealed variation in the magnitude of associations across tasks, with stronger associations for language and executive function (EF) than for other neurocognitive skills (Noble, McCandliss, & Farah, 2007;Noble, Norman, & Farah, 2005). In line with these results, evidence points to large socioeconomic differences in language comprehension and production (e.g., expressive and receptive vocabulary, grammar, phonological awareness), along with moderate to large differences in EF skills, including inhibitory control, working memory, and cognitive flexibility (Lawson, Hook, & Farah, 2017;Pace, Luo, Hirsh-Pasek, & Golinkoff, 2017).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…These studies revealed variation in the magnitude of associations across tasks, with stronger associations for language and executive function (EF) than for other neurocognitive skills (Noble, McCandliss, & Farah, 2007;Noble, Norman, & Farah, 2005). In line with these results, evidence points to large socioeconomic differences in language comprehension and production (e.g., expressive and receptive vocabulary, grammar, phonological awareness), along with moderate to large differences in EF skills, including inhibitory control, working memory, and cognitive flexibility (Lawson, Hook, & Farah, 2017;Pace, Luo, Hirsh-Pasek, & Golinkoff, 2017).…”
mentioning
confidence: 73%
“…In follow‐up work, 3‐year‐olds from lower income families had less than half the vocabulary of their counterparts from higher income families. With these findings replicated in numerous studies, converging evidence indicates that SES‐based variability in linguistic stimulation in the home (especially the quality of language input) accounts partially for socioeconomic differences in children's language development (Pace et al., ). Echoing these behavioral findings, in a recent study using fMRI, less advantaged parents had fewer conversational exchanges with their 4‐ to 6‐year‐olds than more advantaged parents.…”
Section: Mediators Linking Socioeconomic Background With Language Andmentioning
confidence: 91%
“…This heterogeneous factor has been discussed repeatedly in the literature on language acquisition, saliently in Hart and Risley (), who focused on English‐learning American infants, but also in much other work, for instance, that documenting variation among infants growing up in Guatemalan rural households (Klein et al., ). There are numerous pathways through which SES could potentially account for structured variance in input quantity (see Pace, Luo, Hirsh‐Pasek, & Golinkoff, ; Schwab & Lew‐Williams, for recent reviews). To mention just three, all else equal: (a) families with lower SES may experience harsher living conditions, with negative consequences for their emotional well‐being leading to poorer infant–caretaker attachment (e.g., Hackman, Farah, & Meaney, , p. 653 ff.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding variation in mothers' language input is critical because a wealth of evidence suggests that maternal language input is associated with children's vocabulary development (Pace, Luo, Hirsh-Pasek, & Golinkoff, 2017). For instance, children of mothers who use a higher number of word types, meaning more diverse vocabularies, are more likely to have larger vocabularies (Bornstein, Haynes, & Painter, 1998;Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991;Pan, Rowe, Singer, & Snow, 2005).…”
Section: Ses Maternal Linguistic Input and Child Vocabulary Developmentioning
confidence: 99%